A Comparison of Effectiveness of Spiritual Therapy and Acceptance and Commitment Therapy (ACT) on Reducing Existential Anxiety in Women with Breast Cancer - Zahra Zari Moin; Khadijeh Abolmaali Alhoseini; Mohammad reza Seirafi (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2023)
Breast cancer is the most common cancer in women and the second cause of death from cancer. This disease is associated with psychological distress, anxiety, emotional distress, and depression. Therefore, the importance of psychological interventions is revealed to reduce the stressful consequences of breast cancer. The purpose of this study was to compare the effectiveness of spirituality therapy with acceptance and commitment therapy in reducing existential anxiety in women with breast cancer. The research method was quasi-experimental with the pre-test and post-test design and a one-month follow-up with two experimental groups and one control group. The population included women who were referred to the specialized women's cancer center of Khatam al-Anbia Hospital, among them 45 women who had a score of 1.5 standard deviation above the mean on the existential anxiety scale were identified and randomly assigned to three groups and completed Good and Good existential anxiety scale. The first experimental group underwent eight sessions of spiritual therapy and the second experimental group underwent eight sessions of acceptance and commitment therapy. The data were analyzed using MANCOVA and ANOVA with repeated measures. The results showed that the effect of the two methods of spirituality therapy and acceptance and commitment therapy on reducing existential anxiety in women with breast cancer was significant, and there was no significant difference between the effectiveness of the two methods on existential anxiety. It is suggested that health psychologists use spiritual therapy and acceptance and commitment therapy to reduce existential anxiety in breast cancer patients.